Avaliação reológica do óleo de abacate (Persea americana mill) e estudo da estabilidade sob condições de aquecimento e armazenamento à temperatura ambiente - Jorge, Tamara de Souza [UNESP] (2014)
The present study aimed at characterizing the pulp of avocado (Persea americana Mill) varieties Margarida and Hass, as well as extracting the oils from the pulp by centrifugation, determining the rheological behavior, and characterizing and studying oxidative stability and bioactive compounds of the oils during heating and storage at room temperature. The pulp was characterized as to moisture, lipids, proteins, and ashes. The oils were evaluated as to rheological behavior, characterized physico-chemically, and analyzed as to composition of fatty acids, triacylglycerols, phytosterols, tocopherols, and antioxidant activity. A study on oxidative stability and bioactive compounds of oils subjected to thermoxidation process (180 ± 5°C/16 h) and storage (room temperature/12 months) was performed. Hass avocado presented higher level of fatty matter and yield, compared to Margarida avocado. At 40°C, temperature used in the extraction by centrifugation, the oils presented similar viscosity values. The oils showed the same variation in viscosity when subjected to the same temperature variation. Among fatty acids, oleic was predominant in all oils. The main triacylglycerols found confirm the significant quantity of oleic acid present in oils. Amongst phytosterols and tocopherols, β-sitosterol and α-tocopherol were, respectively, the main constituents found in all oils, especially in Margarida. The oils presented similar behavior among DPPH●, FRAP, and ABTS●+ systems, and Margarida oil showed higher antioxidant activity. According to the results obtained in this study, avocado oils presented better behavior during heating process and storage, in Margarida and Hass, respectively. The avocado oils used in this study showed to be inadequate for consumption. Such fact indicates that, in some way, improvements must be done in the process, either during raw material preparation, extraction, or in oil storage